Industrial Processing of Algerian Table Olive Cultivars Elaborated as Spanish Style - Sab, Chafiaa; Romero, Concepción; Brenes, Manuel; Montaño, Alfredo; Ouelhadj, Akli; Medina, Eduardo (Frontiers in Microbiology, 2021)
Olives of Sigoise, Verdale and Sevillana cultivars were elaborated as Spanish-style table olives by four Algerian industries. Despite the differences along the processing, especially during the washing steps, no relationship was found for sugars and polyphenols concentrations among samples. The final pH values reached at the end of the fermentation ranged between 5.04 to 4.27, and the titratable acidity was above 0.4% for all the samples. Lactic and acetic acid were produced in mean concentrations of 0.68 and 0.21 % as a result of lactic acid bacteria (LAB) and yeast metabolism, respectively. However, the presence of butyric, isobutyric and propionic acids was also detected and was related to the growth of non-desirable spoilage microorganisms, responsible of secondary fermentations. The high throughput sequencing of bacterial DNA suggested the dominance of LAB species belonging to genera Lactobacillus, Leuconostoc, Pediococcus, Oenococcus or Enterococcus. The family Enterobacteriaceae was detected during the first days of brining and in only one sample after 120 days of fermentation. Other spoilage microorganisms as Lactobacillus buchneri or genera Pectinatus and Acetobacter, capable of consuming lactic acid, were found and played an essential role in the onset of spoilage. The genera Clostridium and Enterobacter, butyric and propionic acids producers, were responsible for the malodorous fermentation carried out in the industrial samples analyzed. The study concluded that the washing steps should be time reduced to avoid the loss of fermentable matter with the goal to reach a pH < 4.0 after the fermentation and prevent the possibility of growth of spoilage microorganisms and foodborne pathogens.